Pengaruh Penerapan Sistem Informasi Akuntansi, Pemanfaatan Sistem Informasi, Efektivitas Penggunaan Sistem Informasi Akuntansi, Kepercayaan Atas Teknologi Sistem Informasi Akuntansi, Dan Teknologi Informasi Terhadap Kinerja Individu Karyawan - Renaldy Lukiman; JB Widodo Lestarianto (Ultima Accounting : Jurnal Ilmu Akuntansi, 2016)
The purpose of this research was to examine the effect of Implementation of Accounting Information Systems, Use of Information Systems, The Effectiveness of The Use of Accounting Information Systems, Confidence in the Technology of Accounting Information Systems, and Information Technology towards The Individual Employees Performance. The analysis method used in this research is multiple regression analysis. The sample of this research were the employees who work at Manufacturing Company’s Accounting and Finance and using accounting information system. The sample in this research based on nonprobability sampling method, and the sampling technique was convenience sampling. The data used in this research was primary data. The results of this research are: (1) Implementation of Accounting Information Systems has not influence towards The Performance of Individual Employees, (2) Use of Information Systems, The Effectiveness of The Use of Accounting Systems, Confidence In The Technology of Accounting Information Systems, and Information Technology has significant influence towardsThe Performance of Individual Employees, (3) Implementation of Accounting Information Systems, Use of Information Systems, The Effectiveness og The Use of Accounting Information Systems, Confidence in the Technology of Accounting Information Systems, Information Technology simultaneously have significant influence towards Performance of Individual Employees. Key Words: Confidence in the Technology of AIS, Implementation of AIS, Information Technology, Performance, Effectiveness of the Use of Accounting Information System, Use of Information Systems.